Impact of Palm Oil Waste Management Activities in Arongan Village, Kuala Pesisir District, Nagan Raya Regency - Khatrinatasa, Suriani (Journal of Political and Governance Studies, 2025)
Background In general, waste is the residual product from the production process of materials that do not yet have economic or practical value in manufacturing or use. This study discusses the impacts caused by waste, including positive, negative, conscious, and unconscious effects. The purpose of this study is to examine the types of impacts generated and to determine the levels of pollutants present in palm oil waste. Methods This research uses a qualitative approach, with data collected through documentation, observation, and interviews. The data were analyzed using descriptive and analytical methods with an inductive reasoning approach, based on information from ten sources, including the head of PT Socfindo, factory employees, and residents of Arongan Village who assessed the environmental impact of palm oil waste. Results There are several benefits from the positive impact of waste management, including its potential to be processed into fertilizer, and because the resulting waste pollutant does not have a polluting effect on the environment. This is due to the pH, BOD, COD, and TSS of the resulting fatty oil still being low and not exceeding quality standards. Conclusions Based on the data obtained, the authors conclude that the characteristics of the waste produced by the palm oil mill owned by PT Socfindo in Arongan Village are good and appropriate. As for the realized impacts, one of them is the odor generated and the holding pond's barrier that has not met usage standards. PT Socfindo has drafted a plan for constructing pool barriers, but the process has not yet been implemented.